Community based agricultural extension as a participatory organizational learning process in producer organizations: lessons from a case study in rural Colombia - Hering, Johannes (Wageningen University & Research, 2019)
Community-based agricultural extension (CBAE) facilitates the implementation of knowledge in rural communities, often making use of existing organizational structures. Organizational Learning (OL) and Knowledge Management (KM) theory generally explain the mechanisms of the introduction and implementation of knowledge in organizations and how to create a learning culture within them. OL and KM both deal with the adaptation- and learning-process of organizations and could therefore benefit from each other’s body of literature. By carrying out a mix of inductive and deductive analysis of the co-creation process of a CBAE-platform in a Colombian livestock producer organization, this research establishes a link between CBAE and OL/KM. Potentials and limitations of interdisciplinary thinking between the two fields are identified. Based on a qualitative analysis, a knowledge framework that was key to the observed learning processes on ground is evolved. This framework follows a similar logic as suggested in OL/KM theory, where the notions acquire, create, apply, share and store knowledge lie at the center of organizational learning. This analysis suggests adding the themes network, facilitation and participation to this concept. Results indicate that along all layers and stages of the project’s development, the identified knowledge framework provided an underlying structure for the process of integrating knowledge into the organizational memory of the producer organization. It can be concluded that CBAE projects should aim for institutionalizing knowledge by making use of existing organizational structures. OL/KM frameworks provide help to structure and explain this process, if adapted to the context of agricultural extension. The participatory character of CBAE could in turn contribute to OL/KM theory by supporting the process of creating a learning culture in organizations outside the context of agricultural extension. To make optimal use of existing knowledge, a strong practical and theoretical interdisciplinary perspective in the fields of CBAE and OL/KM is recommended.